FAKTOR PENGHAMBAT PEMBERIAN ASI EKSKLUSIF PADA IBU BEKERJA DI KOTA BLORA - Yanik Muyassaroh; Rizky Amelia; Komariyah Komariyah (JURNAL KEBIDANAN, 2018)
Breastfeeding is one of the first steps for a human being to get a healthy and prosperous life. Data from the Blora District Health Office, the number of infants aged 6-24 months was 1,063 babies. Of these figures, exclusive breastfeeding rates are still around 75%. The exclusive breastfeeding coverage is still below the target in accordance with the Republic of Indonesia Law No. 25 of 2000 concerning the National Development Program (Propenas) in 2000-2004, which states the level of achieving exclusive breastfeeding by 80%. The 2012 Indonesian Demographic Health Survey (IDHS) shows that 57% of the workforce in Indonesia are women. In Blora City, there are already ASI corner facilities in various fields of work, facilities and different policies, but still not supporting the mastery of ASI. Data from the Blora District Health Office, the number of infants aged 6-24 months was 1,063 babies. This research is a quantitative observational analytic study, a cross-sectional approach with a population of 72 people. Samples were taken by Total Sampling. The analysis used is Chi-Square analysis and Logistics regression. The results showed there was a positive and statistically significant effect between policies (OR = 0.043; CI 95% 0.005-0.375; p = 0.004), working hours (OR = 0.049; CI 95% 0.003-0.733; p = 0.029), availability of places pumping breast milk (OR = 0.034; CI 95% 0.004-0.290; p = 0.002) and leadership support with exclusive breastfeeding (OR = 0.057; CI 95% 0.006-0.526; p = 0.012). It is recommended that the Health Service and Puskemas can work together with companies / factories / places of work to improve facilities and infrastructure that can support working mothers in breastfeeding.